Choriocarcinoma of uterine cervix with cerebral and lung metastasis - Ansari, MA; Pokhrel, LR; Thapa, R; Shrestha, DM; Pradhan, S (Journal of Institute of Medicine Nepal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, April, 2009; 31:1 26-29